Steady-state voltammetric characterization and simulation-aided study of the mass transfer enhancement at conical W/WO2 ultramicroelectrodes. (10th January 2022) - Bruno-Mota, Uriel; Rodriguez-Hernández, Ingrid Nayeli; Doostkam, Rasool; Soucy, Patrick; Navarro-Pardo, Fabiola; Orozco, Germán; Yurtsever, Aycan; Tavares, Ana C.
Highlights: Unshielded, conical, sharp W/WO2 ultramicroelectrodes are investigated. Cyclic voltammetry shows higher electroactive/geometric area ratio at the apex. Simulations show higher flux of species at the apex of conical ultramicroelectrodes. The radius of curvature has a higher impact than the aspect ratio on the flow. Abstract: Ultramicroelectrodes (UMEs) have demonstrated their utility in different applications, ranging from probing chemistry to high-resolution electrochemical imaging. Conical UMEs with the apex in the nanometer range are of special interest because their geometrical features may allow the study of single/few nanoparticles, single entities, or electrochemical reactions occurring in the inner structures of living cells which are difficult to access with other types of UMEs. However, there is a lack of experimental studies with individual unshielded conical electrodes aiming at quantifying the impact of the geometry and dimensions on their electrochemical response. In this work, W / WO2 conical UMEs with aspect ratios ranging from 6.6 to 22 and apexes with nm-size dimensions were prepared by electrochemical etching of tungsten wires through an induced dynamic meniscus regime, and in one case followed by focused ion beam milling. The electrodes were characterized by scanning electron microscopy and by cyclic voltammetry in 5 mM [Fe (CN)6 ] 3− and 5 mM [Fe (CN)6 ] 4− in 0.5 M KCl as a function of the depth of the UME immersed in the electrolyte solution. Computational fluid dynamics simulations were used to investigate the mass transfer of the electroactive species at the vicinity of the electrodes. Analytical expressions to predict the steady-state current of conical electrodes with aspect ratios from 3 to 22 and radius of curvature below 110 nm were also derived. It was found that the ratio of the electrochemical surface area to the geometric one rapidly increases when the depth of the UME's in solution is lower than 15 µm, in agreement with a rapid increase of the magnitude of the total flux towards the UMEs apex. Both experimental and simulation studies point to the radius of curvature as the most important parameter determining the rate of the oxidation / reduction of the [Fe (CN)6 ] 3− / [Fe (CN)6 ] 4− species at non-insulated conical UMEs with high aspect ratio. Graphical abstract: Image, graphical abstract .